IMPLEMENTASI PROGRAM AKSI PARTAI AMANAT NASIONAL PASCA PEMILU 2009 - Johanes " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Political Party is single united Ideological unit which grown up and expand through living in democratic system of society. The existence of Political party proved very important to build equality and welfare of society. Partai Amanat Nasional(PAN) as one of politic party which involved in year 2009 General Election has strategical position to participated in increasing and development of Riau Province, because in 2009 Election PAN won large portion in Riau Parlementary seat. These Journal provide analytical view action of PAN programs after 2009 General Election and explain PAN programs as its Political Party form. These Journal using Qualitative and Analitic Descriptive view of method research. The result of research showed us PAN programs included active involvement in Election of Riau Governor and other strategic programs which synchronized with Riau Province development.Key Word: Political Party, Program and General Election